Does Temptation Associate with Unethical Intention? A Mediating Role of Monetary Intelligence: Evidence from MBA Students in Nepal - Dabadi, Bhanu; Pokhrel, Laxman (Quest Journal of Management and Social Sciences, 2023)
Purpose- The purpose of this study is to examine the mediating role of Monetary Intelligence (MI) between Temptation (TEM) and Unethical Intention (UI) among MBA students in Nepalese Business Schools. Design/ Methodology/ approach- The research applied a cross-sectional survey research design to collect data from 341 MBA students in Nepali Business Schools. The purposive sampling method was used to reach the respondents. The Partial Least Square Structural Equation Modelling (PLS-SEM) was applied to test the stated hypotheses. Finding- The study revealed that TEM has a significant influence on UI. However, MI and TEM do not significantly influence UI. Likewise, the specific indirect effects and total effects are not significant. Therefore, the results of the mediational analysis illustrated no effect (no mediation) results. Practical implications- This study focuses on understanding the significance of MI in relation to TEM to trigger UI among MBA students at Nepali Business Schools. This paper paves the path for undertaking complex higher-order constructs in the existing PLS-SEM literature. Likewise, human resource managers could develop their recruitment, training, and performance appraisal mechanism based on understanding the temptation of prospective employees and their possibility of engaging in unethical behaviours. Originality- This paper has investigated Temptation (reflective-formative), Monetary Intelligence (reflective-formative), and Unethical Intention (reflective-reflective) to explain the mediational mechanism of MI with TEM and UI. The present study is among the earliest studies to examine unethical intention in the Nepali context. Keywords: Monetary intelligence, formative construct, reflective construct, temptation, unethical intention JEL: M10